Study of Mechanical Structural Optical and Luminescence Properties of silicate and phosphate-based Tint Glass Matrix for Photonic OP to electronic and Building Envelope Applications : - Mahapatra, Debajyoti (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Ceramic Engineering